Efeito do silicato de potássio em plantas de mamoeiro sobre a infestação do ácaro-rajado, tetranyhcus urticae koch - Catalani, Gabriela Christal [UNESP] (2015)
The twospotted spider mite, Tetranychus urticae Koch, it is a principal pest of papaya crop and its main control method is the chemical, as an alternative method has been researched host plant resistance induction, which involves the activation of mechanisms defense of existing plants. This control strategy has potential for use in integrated pest management and silicon is one of the possibilities to use. The objective of the work was to determine whether potassium silicate application on papaya plants induces resistance to the twospotted spider mite, T. urticae, and decreases its infestation. In the first experiment, the experiment was designed in randomized blocks with six treatments and eight repetitions, with each repetition consists of a papaya plant artificially infested with T. urticae females from laboratory creation. Doses of potassium silicate were tested, foliar: T1 - control; T2 - 2 L ha -1 - 3 sprays; T3 - 2 L ha -1 - 2 sprays; T4 - 4 L ha -1 - 3 sprays; T5 - 4 L ha -1 - 2 sprays; T6 - 4 L ha -1 - 1 spray. Three evaluations were carried out by counting the number of eggs, mites and exuviae of T. urticae present along the main vein of a leaf infested by installment. In the second experiment, in the greenhouse, the experiment was designed in randomized blocks with four treatments and eight repetitions, each repetition consisting of one papaya plant artificially infested with T. urticae females from laboratory creation. Doses of potassium silicate were tested, on soil and sprayed on leaves: T1 - control; T2 - 4 L ha -1 with 4 foliar sprays; T3 - 4 L ha -1 with 9 foliar sprays and T4 - 8 L ha -1 in the soil with 7 applications. Four evaluations were carried out by counting the number of eggs, mites and exuviae of T. urticae present along the main vein of a leaf infested by installment. In laboratory, were built fertility life tables of T. urticae fed papaya leaves the plants of receiving application of ...